Analisis Tegangan Pada Rangka Mobil Off Road Menggunakan Metode Elemen Hingga Dengan Software SolidWorks - Suryanto, Hendri; Herraprastanti, Eva Hertnacahyani (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2023)
The chassis is the main part of a vehicle that functions to hold all components and passengers and must be able to withstand the loads that occur without experiencing excessive deflection or deformation. Off-road cars are designed to be able to pass on unpaved roads or terrain or rocky surfaces. With such terrain, it will put an excessive burden on the car, especially on the frame. The frame will be subjected to greater bending and torsional loads if the car is used on an uneven surface. For that we need a frame that is strong and rigid so that it is safe for the driver and other car components. In this study, an analysis of the stress that occurs on the frame of the TM D3 Off-Road Car was carried out to determine its strength. The analysis was carried out numerically using the finite element method using SolidWorks software. The results of the analysis show that under a static load of 3000 N, the frame is still in a safe condition because the stress that occurs in the frame is below the yield stress value of the material used, while at a torsional loading of 500 N.m, the frame is in an unsafe condition because the stress that occurs exceeds the value the yield stress of the material used. After modifying the frame, the simulation results with 500 N.m torsional loading show that the stress that occurs in the frame is in a safe condition.